Estimating National-Level Exposure to Antineoplastic Agents in the Workplace: CAREX Canada Findings and Future Research Needs. Issue 6 (8th June 2017) - Hall, Amy L.; Demers, Paul A.; Astrakianakis, George; Ge, Calvin; Peters, Cheryl E.
Abstract: Objectives: Occupational exposure to antineoplastic agents occurs in various environments and is associated with increased cancer risk and adverse reproductive outcomes. National-level information describing the location and extent of occupational exposure to antineoplastic agents is unavailable in Canada and most other countries. CAREX Canada aimed to estimate the prevalence and relative levels of occupational exposures to antineoplastic agents across work setting, occupation, and sex. Methods: 'Exposure' was defined as any potential for worker contact with antineoplastic agents. Baseline numbers of licensed workers were obtained from their respective professional bodies. For unlicensed workers, Census data or data extrapolated from human resources reports (e.g., staffing ratios) were used. Prevalence was estimated by combining population estimates with exposure proportions from peer-reviewed and grey literature. Exposure levels (classified as low, moderate, and high) by occupation and work setting were estimated qualitatively by combining estimates of contact frequency and exposure control practices. Results: Approximately 75000 Canadians (0.42% of the total workforce) are estimated as occupationally exposed to antineoplastic agents; over 75% are female. The largest occupational group exposed to antineoplastic agents is community pharmacy workers, with 30200 exposed. By work setting, 39000 workers (52% of all exposed) are located in non-hospital settings; the remaining 48% are exposed in hospitals. The majority (75%) of workers are in the moderate exposure category. Conclusions: These estimates of the prevalence and location of occupational exposures to antineoplastic agents could be used to identify high-risk groups, estimate disease burden, and target new research and prevention activities. The limited secondary data available for developing these estimates highlights the need for increased quantitative measurement and documentation of antineoplastic agent contamination and exposure, particularly in work environments where use is emerging.